Effects of iron surface pretreatment on sorption and reduction kinetics of trichloroethylene in a closed batch system - Jung Lin, Chin; Lo, Shang-Lien (Water research (Oxford), 2005)
The decline of trichloroethylene (TCE) in a metallic iron–water system results from the combination of reduction reaction and sorption onto iron surfaces. Sorption, particularly by highly impure iron, accelerates the removal of TCE from the aqueous phase, but delays the prevalence of steady-state conditions. In this case, an overly high value of reaction rate constant in the design of a treatment system would be used. In this work, the effects of an iron surface with 8.0% C, 6.1% O and 0.8% Si separately following HCl-washing and H 2-reducing pretreatment on sorption and reduction rates were examined. The amounts of both aqueous and sorbed TCE were measured using a modified solvent-extraction method. TCE sorption onto an iron surface, as quantified by the Langmuir sorption maximum, followed the trend H 2-reduced Fe 0>HCl-washed Fe 0>untreated Fe 0 (0.887, 0.365 and 0.311 mg/g, respectively). Measurements of the concentration of sorbed TCE revealed that about 34–37% of the initial mass of TCE in the aqueous phase was removed by sorption by H 2-reduced Fe 0, 16–19% was removed by HCl-washed Fe 0 and 13–16% was removed by untreated Fe 0. A combination of new and previously reported data on cast iron's capacity to sorb TCE revealed a linear relationship between this capacity and the C fraction in the surface of the iron, with the coefficient of determination ( r 2 ) exceeding 0.99. The first-order observed rate constants ( k obs) of the reduction of TCE in contact with Fe 0 were obtained from the slope of a plot of total TCE loss rate ( - d C T / d t ) versus the amount of TCE in the aqueous phase ( C w) using linear least-squares analysis. The k obs values were 0.080, 0.148 and 0.191 h −1 for untreated, HCl-washed and H 2-reduced Fe 0, respectively. Normalized to iron surface area concentration, the specific rate constants ( k SA) were 2.37×10 −3 , 2.31×10 −3 and 5.62×10 −3 h −1 m −2 L, respectively. The results indicated that HCl-washing approximately doubled k obs, primarily because of the increase in the surface area of the iron, and it slightly decreased k SA due to rapid corrosion during the rinsing process. Both the number of reactive sites and the sorption capacity per unit iron surface area through the H 2-reducing pretreatment were increased due to the reduction of iron oxide layer and the carbonization of carbon-containing subjects on the iron's surface. Hence, the H 2 reduction of cast iron promotes the removal of TCE from contaminated water by the concurrent sorption and reduction.